2017
DOI: 10.3386/w23368
|View full text |Cite
|
Sign up to set email alerts
|

Capital Accumulation, Private Property and Rising Inequality in China, 1978-2015

Abstract: NBER working papers are circulated for discussion and comment purposes. They have not been peer-reviewed or been subject to the review by the NBER Board of Directors that accompanies official NBER publications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
70
2
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(78 citation statements)
references
References 16 publications
1
70
2
5
Order By: Relevance
“…It is also worth stressing that inequality levels in the Middle East appear to be significantly larger than those observed in giant countries with much larger populations such as China and India (Figures a and 2b). Here we use inequality estimates that were recently constructed for China and India by Piketty, Yang and Zucman () and Chancel and Piketty (). These estimates are obviously far from perfect, but they probably tend to minimize the gap with the Middle East (in particular, we have access to more extensive income tax data for China and India than the for the Middle East).…”
Section: Main Results: Extreme Concentration Of Income In the Middle mentioning
confidence: 99%
See 1 more Smart Citation
“…It is also worth stressing that inequality levels in the Middle East appear to be significantly larger than those observed in giant countries with much larger populations such as China and India (Figures a and 2b). Here we use inequality estimates that were recently constructed for China and India by Piketty, Yang and Zucman () and Chancel and Piketty (). These estimates are obviously far from perfect, but they probably tend to minimize the gap with the Middle East (in particular, we have access to more extensive income tax data for China and India than the for the Middle East).…”
Section: Main Results: Extreme Concentration Of Income In the Middle mentioning
confidence: 99%
“…For this, we follow common methods that involve the combination of national accounts, surveys, and fiscal registries in a consistent manner to produce distributional national accounts . The method has already been applied to the US (Piketty et al, ), France (Garbinti et al, ; ), China (Piketty et al, ), and Russia (Novokmet et al, ). Although there are similarities across countries, lessons can be drawn from specific cases to help produce new databases for future works, in a context of scarcity of data.…”
Section: Introductionmentioning
confidence: 99%
“…Alstadsaeter et al (2016) show that business income reported on individual income tax returns is responsive to tax changes. A wave of recent studies attempts to compute more comprehensive inequality statistics by distributing all of the national income recorded in the national accounts (including corporate retained earnings, and all other legally tax-exempt income); see, e.g., Piketty, Saez and Zucman (2016), Garbinti, Goupille-Lebret and Piketty (2017), and Piketty, Yang and Zucman (2017). These "distributional national accounts" attempt to take into account tax avoidance, but not yet tax evasion (as national income itself is under-estimated when households hide assets abroad; see Zucman, 2013).…”
Section: Tax Evasion By the Wealthy: Evidence From Leaksmentioning
confidence: 99%
“…Appendix K shows that introducing competition in our model does not affect the comparative 45 Instead, HSBC was fined $1.92 billion, in a year when its pretax profits reached $22.6 billion. 46 In the world's two largest economies, the United States and China, top wealth shares have increased significantly since the beginning of the century (Saez and Zucman, 2014;Piketty, Yang, Zucman, 2017). Forbes magazine data suggest that the wealth of global billionaires is rising faster than world wealth (Piketty, 2014).…”
Section: A Model Of Tax Evasion and Inequalitymentioning
confidence: 99%
“…For example, in the neo-Marxists framework productive assets also include labor power, organizations, and skills (Wright 1985;Lin and Wu 2010). 9 See Piketty and al. (2017) for evidence of the rising capital share in national income in China.…”
mentioning
confidence: 99%